2016
DOI: 10.1002/arco.5097
|View full text |Cite
|
Sign up to set email alerts
|

Petrographic analyses of sand temper/inclusions in ceramics of Kikiniu, Kikori River and modern sand samples from the Gulf Province (Papua New Guinea)

Abstract: The archaeological site of Kikiniu (a.k.a. Kulupuari) in the mid-reaches of the Kikori River, Gulf Province (Papua New Guinea) contains a rich assemblage of ceramic sherds dating to 1550-1000 calBP. This is a region for which there is no ethnographic and no prior archaeological evidence of ceramic manufacture, but for which during the ethnographic period premade pottery vessels are well known to have been imported en masse from long-distance seafarers from Yule Island and Port Moresby. Here we present initial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The use of optical microscopy and scanning electron microscope analyses in ceramic sand-temper analyses helps to underline the importance of geology to an understanding of ancient peoples and their cultures. This study has shown that the use of temper to reconstruct exchange networks is illuminating and gathering momentum in the Pacific Islands [3,6,15,41,42] and elsewhere in the world [8,43,44].…”
Section: Discussionmentioning
confidence: 99%
“…The use of optical microscopy and scanning electron microscope analyses in ceramic sand-temper analyses helps to underline the importance of geology to an understanding of ancient peoples and their cultures. This study has shown that the use of temper to reconstruct exchange networks is illuminating and gathering momentum in the Pacific Islands [3,6,15,41,42] and elsewhere in the world [8,43,44].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, minerals/inclusions were quantified as to their abundance, borrowing the idea of point counting from sedimentary petrology, that is to count the grain types/clay matrix falling beneath the intersection points of a rectilinear grid on the printed out 2000 × 1875 pixels SEM maps, resulting in a 100-point count for each SEM map. While frequency counting has been used most commonly in the Pacific (Dickinson 2006), the two other studies to have employed petrographic analysis of temper on the south coast of Papua New Guinea (Marsaglia et al 2016;Worthing 1980aWorthing , 1980bWorthing , 1982 both employed point counting.…”
Section: Methodsmentioning
confidence: 99%
“…Because of this connection between pottery and trade, there have been a number of pottery sourcing or characterisation studies completed on the south coast of Papua New Guinea (e.g. Bickler 1997;Frankel et al 1994;Marsaglia et al 2016;Rye and Duerden 1982;Summerhayes and Allen 2007;Sutton et al 2019;Vigalys and Summerhayes 2016;Worthing 1980aWorthing , 1980bWorthing , 1982Worthing and Swadling 1980). In particular, multiple sourcing studies have aimed at establishing a link between the Port Moresby region as a pottery-producing area and Gulf Province sites known historically or assumed to have been pottery consumers within the hiri trade network, although these studies have varied in terms of both methodology and results.…”
Section: Sourcing Pottery On the Papuan South Coastmentioning
confidence: 99%
See 2 more Smart Citations